Dual Function Characterisation of the 4‐Cysteine Hepcidin in the Antarctic Toothfish Dissostichus mawsoni - Mingli Liu; Ruiqin Hu; Wanying Zhai; Jihui Yang; Jingwen Ma; Peng Hu; Qianghua Xu; Liangbiao Chen (Journal of Fish Diseases, 2026)
Hepcidin is a cysteine‐rich peptide that functions both as an antimicrobial peptide and a central regulator of iron homeostasis in vertebrates. Structurally, it consists of an N‐terminal signal peptide, a propeptide region and a C‐terminal bioactive mature peptide. The canonical mature hepcidin contains eight conserved cysteine residues that form four disulfide bonds, stabilising a characteristic β‐sheet hairpin‐like structure. In the Antarctic toothfish ( Dissostichus mawsoni ), which inhabits extremely cold marine environments, a unique hepcidin variant was identified possessing only four cysteine residues, designated dm_4cyshep. To evaluate the antimicrobial function of the dm_4cyshep peptide, the minimum inhibitory concentration (MIC) assays and flow cytometry analyses were performed. The peptide demonstrated binding affinity and bactericidal activity against a range of Gram‐positive and Gram‐negative bacteria, with distinct MIC values observed for different strains. Furthermore, overexpression of dm_4cyshep in a hepcidin‐deficient zebrafish model markedly reduced systemic iron accumulation, indicating a conserved role in iron regulation. These results demonstrate that despite the reduced number of cysteine residues, dm_4cyshep retains both antimicrobial and iron‐modulatory functions, underscoring its potential as an immune effector molecule. This study enhances the understanding of the structural and functional diversity of fish hepcidins and identifies a promising candidate for improving disease resistance in aquaculture.